Kinetic Study of Iodination of Propanone in Different Acidic Media by Using Colorimeter - Sharma, Nitin; Alam, Tanveer; Kumar, Ashok (Current Physical Chemistry, 2022)
Aims: Kinetic study of iodination of propanone in different acidic medium by using colorimeter. Background: The kinetic experimentation of iodination of propanone has been done in presence of different acid such as sulphuric acid, hydrochloric acid and acetic acid. The rate law of the iodination of propanone in acidic medium is determined by observing the disappearance of the brownish yellow colour of iodine in aqueous solution. Objective: Preparation of standard solution, Determination of absorbance of iodine solution at λmax= 480 nm, Kinetic study of iodination of propanone at different acidic medium. Methods: The kinetic analysis of this reaction has been investigated by colorimetry. The extent of the reaction has been monitored by measuring the absorbance of reaction mixture after a suitable time interval. Results: The rate law expression has been determined to be rate = k [propanone]00.728 [acid]0. The rate of iodination of propanone in the presence of different acidic medium is in the order of H2SO4 > HCl > CH3COOH. Conclusion: The rate of the reaction has been found to be independent of the concentration of iodine, i.e., a zero-order reaction with respect to iodine; however, it depended upon the concentration of propanone and the acidic catalyst. In this experimental technique, the consumption of chemicals is minimal.
Keywords: absorbance